대학교 교양 강좌로서 라틴어 교육의 내용과 방법 - 손윤락(Sohn, Yun-Rak) (교양교육연구, 2020)
라틴어는 서구 문화의 공통 모체이며 다양한 지식의 기본 용어를 제공하는 학문 도구로서, 동양에서의한문과 같이 서양의 학문과 지식 일반에 쓰임이 많기에 서양에서는 중등교육 과정에서부터 교육이이루어진다. 반면, 한국에서 라틴어 교육은 대학교에서 시작되며 모두 교양 강좌로 열린다. 본고는라틴어 교육이 위기에 처한 한국의 현실에서 라틴어 교육의 내용과 함께 교수 방법에서 변화가 필요하며, 문법 위주의 수업에서 문화적 접근으로의 전환을 주장한다. 본고는 필자가 2019년에 수행한 “한국의 대학 교육에서 라틴어 교육의 현황” 연구에서 밝힌 구체적인자료를 바탕으로, 대학교 교양 수준의 강좌로서 라틴어 교육의 실제 내용과 그것에 연계된 세 가지방법론을 제시한다. 첫째, 언어사적 접근으로서, 인도유럽어의 전통과 로망스어의 모어이자 서양 언어들의 뿌리로서 라틴어에 대한 이해를 언급한다. 둘째, 문법적 접근으로서, 음운론, 형태론, 통사론에서전통적인 라틴어 교육의 내용을 설명한다. 셋째, 문화적 접근으로서, 교양 강좌로 이루어지는 라틴어수업에서 문화적 접근의 필요성을 주장하며, 라틴어 교육에서 로마 문화와 문학 콘텐츠 활용의 방법을다룬다. 결론으로, 본고는 한국 대학의 교양교육이 처한 상황과 함께 라틴어 교육의 세계적인 추세에맞추어 라틴어 교육에서 문법, 문학, 문화 콘텐츠가 조화를 이루도록 하는 것이 바람직함을 도출한다. 라틴어 교육이 문화적 접근으로 방법론적 전환을 이룬다면, 위기에 처해 있는 라틴어가 학문 도구로서의 가치만이 아니라 글로벌 시대에 요구되는 세계시민성과 문화지수 함양을 위해서도 그 필요성을인정받고 우리나라 대학교의 교양교육에서 제 자리를 잡는 계기가 될 것이다. This paper is a study on the contents and the method of Latin language education in Korean universities as a liberal arts course. The introduction reviews the status of the Latin language in Korea, which is one belonging to an extreme minority where language education is concerned, and discusses the importance of the teaching method of Latin, along with its contents. The main part presents three methodologies linked to the educational contents of Latin. i) As a linguistic historical approach, it refers to the tradition of an Indo-European language and to the status of Latin as the parent language of the Romance languages, and also as the root of Western languages. ii) As a grammatical approach, it explains the contents of traditional Latin education in terms of phonology, morphology and syntactic theory. iii) As a cultural approach, it asserts the need of a cultural approach in Latin language education, which is given as a liberal arts course in non-Western countries such as Korea, and deals with the method of utilizing the contents of Roman culture and literature in Latin education. This paper concludes that it is desirable for grammar, literature and cultural content to be harmonized in Latin education, and presents some concrete methods for achieving this end. This study will contribute to the establishment of the Latin language in university education in Korea, which is of high value not only as an academic tool, but also as an approach to world-citizenship in the global era. KCI Citation Count: 0